Images of the future city time and space for sustainable development - Höjer, Mattias 1966- (Springer, 2011)
The future Western city look like if energy use per capita was reduced by sixty percent? This is the overarching question researchers have addressed in a major backcasting study carried out in Stockholm in recent years, and their answers are revealed in this book. In Images of the Future City: Time and Space For Sustainable Development, fourteen researchers from numerous disciplines offer details on a variety of aspects of a future sustainable city, including travel, housing, eating, time use, consumption and urban form. The result is a complete illustration of what it could be like to live in a city based on sustainable energy use, with Stockholm 2050 as the geographical and temporal setting. This book is an ideal complement to studies showing the potentially devastating ecological effects of climate change, studies trying to calculate the costs of climate change, and studies trying to identify the most pressing needs in preparing for the new climate. In Images of the Future City: Time and Space For Sustainable Development, fourteen researchers from numerous disciplines offer details on a variety of aspects of a future sustainable city, including travel, housing, eating, time use, consumption and urban form. The result is a complete illustration of what it could be like to live in a city based on sustainable energy use, with Stockholm 2050 as the geographical and temporal setting. This book is an ideal complement to studies showing the potentially devastating ecological effects of climate change, studies trying to calculate the costs of climate change, and studies trying to identify the most pressing needs in preparing for the new climate.